2015
DOI: 10.1097/hjh.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of the natriuretic peptide system to weight loss and exercise in overweight or obese patients

Abstract: We conclude that physical exercise acutely increases ANP release in obese patients, whereas modest diet-induced weight loss primarily affects ANP clearance mechanisms. Interventions combining weight loss and regular physical exercise may be particularly efficacious in reversing obesity-associated relative natriuretic peptide deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…However, weight loss studies, either involving caloric restriction or gastric bypass surgery, indicated increased systemic NP levels (i.e. N-terminal proBNP) (210)(211)(212)(213)(214)(215), which was not confirmed in all studies (200,216,217). In the comparison of these interventions, it was recently shown that the amount of weight loss is associated with the increase in systemic NP concentrations (218).…”
Section: Lifestyle Interventions and Natriuretic Peptidemediated Metamentioning
confidence: 99%
“…However, weight loss studies, either involving caloric restriction or gastric bypass surgery, indicated increased systemic NP levels (i.e. N-terminal proBNP) (210)(211)(212)(213)(214)(215), which was not confirmed in all studies (200,216,217). In the comparison of these interventions, it was recently shown that the amount of weight loss is associated with the increase in systemic NP concentrations (218).…”
Section: Lifestyle Interventions and Natriuretic Peptidemediated Metamentioning
confidence: 99%
“…Considering 304 that AT and systemic inflammation are associated with insulin resistance [74], this could be 305 one mechanism by which ANP preserves insulin sensitivity in humans. Two studies also 306 suggested that ANP enhances the secretion of the pro-insulin sensitizing adipokine normalize NPRC expression in white adipose tissue [93]. It was shown that the early phase 371 of weight loss induced by calorie restriction is associated with natriuresis, reduction in blood 372 pressure and a doubling of plasma ANP levels in overweight normotensive subjects [94].…”
Section: Insulin Sensitivity 288mentioning
confidence: 99%
“…e cardiac natriuretic peptide system directly reduces renin and aldosterone secretion and antagonizes AngII and aldosterone effects on target cells [26]. A number of studies reported reduced levels of circulating natriuretic peptides in obese subjects with hypertension [29,30] and without hypertension [31][32][33]. We found that in obese hypertensive patients, the intake of glucose with NaCl was associated with a significant increase in serum Na and that obese hypertensive patients had higher serum Na and AngII compared with nonobese patients.…”
Section: Discussionmentioning
confidence: 58%